2014
DOI: 10.15516/cje.v16i0.643
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Teachers’ Beliefs about Learning/Istraživanje o uvjerenjima što ih učitelji imaju o učenju

Abstract: The aim of this study was to investigate teachers beliefs about learning. So, we investigated the level of teachers beliefs about the traditional and constructivist approach (cognitive, social and radical). Further, it was questioned how teachers developed qualifications needed for the constructivist approach. The study was conducted on 233 teachers working in the city centre of Gaziantep in Turkey during 2011-2012 school year. Beliefs about Learning Scale, developed by the researchers, was used for data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This implies that the majority of degree holders are in general more experienced than diploma holders. Nevertheless, a study report indicated that as the teachers' seniority increases, the level of their beliefs about traditional learning also increases [ 39 ]. This implies that the primary teachers' positive belief in the current study stands against the result found elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the majority of degree holders are in general more experienced than diploma holders. Nevertheless, a study report indicated that as the teachers' seniority increases, the level of their beliefs about traditional learning also increases [ 39 ]. This implies that the primary teachers' positive belief in the current study stands against the result found elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the efforts to train teachers who can apply CU-based curricula since then, some studies in the literature concluded that many teachers did not feel competent, did not implement the curriculum in a proper manner, or encountered various problems (e.g. Adanur-Kudal & Altun, 2012;Bay et al, 2014;Çaycı & Altunkeser, 2015;Çiftçi et al, 2013;Çubukçu, 2006;Gür-Erdoğan & Kanbur, 2013;Özaydın-Özkara, 2017;Yücel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%